Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 198238 species occurrences available in GBIF matching the query: { "InstitutionCode" : [ "is LSU" ] } The dataset includes 198238 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001162-160526112335914/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences